Having Everyone in the Boat May Sink it - Interest Group Involvement and Policy Reforms - Kira Boerner (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2005)
In many countries, governments involve interest groups at early stages of political decisionmaking. The idea of this is to enhance the legitimacy of the policy decision and to curb later opposition to the implementation of the policy. We show that the way and timing of interest groups involvement can be crucial for the scope and success of policy reforms. When interest groups influence both the policy choice, or legislation, and the subsequent decision on the implementation of the policy, their early involvement may lead them to oppose the reform more than if they had been excluded from the legislation stage.
urn:nbn:de:bvb:19-epub-730-7
Keywords: D72; D78; H51; 330; policy choice; policy implementation; common agency; lobbying